The “Don’t come/Go back home” continuum: the use of storytelling in Migration Information Campaigns - Balty, Cécile; Mistiaen, Valériane; Van Neste-Gottignies, Amandine; Calabrese, Laura (Revista da ABRALIN, 2021)
Campaigns to encourage return or deter migration have become a priority for European governments, revealing a new way of managing migration flows to Europe. If scholars from social sciences have investigated these campaigns, no study in the field of discourse analysis addressed the argumentative discursive mechanisms at work in shaping migrants’ perceptions. The present research analyses the use of storytelling in migration information campaigns (MICs) by comparing two online European campaigns: a dissuasive campaign (tellingtherealstory.org) and a persuasive campaign (retourvolontaire.be). First, the discursive features of each website are described, highlighting the central place given to migrant’s stories. Second, a narrative and lexical analysis is conducted on these stories to investigate the way in which they constitute the argumentative dimension of these campaigns’ discourses. The results show that the stories of both dissuasive and persuasive campaigns converge towards the same moral: migratory projects are doomed to fail. These migration information campaigns can be seen as part of what we call the “Don’t come/Go back home” continuum